Impacts of urbanization on insect herbivory and plant defences in oak trees. Issue 1 (19th September 2018) - Moreira, Xoaquín; Abdala‐Roberts, Luis; Berny Mier y Teran, Jorge C.; Covelo, Felisa; de la Mata, Raúl; Francisco, Marta; Hardwick, Bess; Pires, Ricardo Matheus; Roslin, Tomas; Schigel, Dmitry S.; ten Hoopen, Jan P. J. G.; Timmermans, Bart G. H.; et al.
Abstract : Systematic comparisons of species interactions in urban versus rural environments can improve our understanding of shifts in ecological processes due to urbanization. However, such studies are relatively uncommon and the mechanisms driving urbanization effects on species interactions (e.g. between plants and insect herbivores) remain elusive. Here we investigated the effects of urbanization on leaf herbivory by insect chewers and miners associated with the English oak Quercus robur by sampling trees in rural and urban areas throughout most of the latitudinal distribution of this species. In performing these comparisons, we also controlled for the size of the urban areas (18 cities) and gathered data on CO2 emissions. In addition, we assessed whether urbanization affected leaf chemical defences (phenolic compounds) and nutritional traits (phosphorus and nitrogen), and whether such changes correlated with herbivory levels. Urbanization significantly reduced leaf chewer damage but did not affect leaf miners. In addition, we found that leaves from urban locations had lower levels of chemical defences (condensed and hydrolysable tannins) and higher levels of nutrients (nitrogen and phosphorus) compared to leaves in rural locations. The magnitude of urbanization effects on herbivory and leaf defences was not contingent upon city size. Importantly, while the effects of urbanization on chemical defences were associated with CO2 emissions, changes in leaf chewer damage were not associated with either leaf traits or CO2 levels. These results suggest that effects of urbanization on herbivory occur through mechanisms other than changes in the plant traits measured here. Overall, our simultaneous assessment of insect herbivory, plant traits and abiotic correlates advances our understanding of the main drivers of urbanization effects on plant–herbivore interactions.